CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) Independent Science Panel Conflict of Interest Policy - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
The CCAFS Independent Science Panel (ISP) approved an ISP conflict of interest policy at its meeting in Rome, Italy on 10 October 2013.